Retrospective Case Reports of Anemic Pregnant Women Receiving Intravenous Ferric Carboxymaltose: Experience from a Tertiary Hospital in Spain - Rafael Aporta Rodriguez; Mariola García Montero; Jose Pablo Lorente Aporta; Carolina Gallego Luque; Alfonso Chacón Mayor; Jose Aragón Ruiz; Virginia Torres Degayón; Claudia García Jimenez; Guadalupe Sanchez Sanchez (Hindawi Limited, 2016)
Iron deficiency and iron deficiency anemia during pregnancy call for safe treatment options that raise maternal hemoglobin levels and counterbalance iron demand and blood volume expansion while minimizing risks for the growing fetus. This retrospective study describes experience with intravenous ferric carboxymaltose given to pregnant women in a tertiary hospital in Spain. In a 5-year period, 95 pregnant women who had pretreatment hemoglobin <10 g/dL and at least one time of ferric carboxymaltose administration during pregnancy were included. Main outcome measures were week of pregnancy at iron administration, Hb levels before and after treatment, neonatal 5-minute Apgar scores, and birth weight. The majority received one dose of ferric carboxymaltose (1000 mg iron) during advanced pregnancy (median 31 weeks; interquartile range [IQR]: 27; 37 weeks) with minor to no adverse outcomes. Overall, median Hb increased from 8.5 g/dL (8.1; 8.9 g/dL) before treatment to 11.0 g/dL (9.9; 11.7 g/dL) after treatment. Normal Apgar scores were observed in all 97 infants (median birth weights 3560 g, 3270, and 3798 g). Four women received ferric carboxymaltose in the first trimester and twenty-eight during the second trimester without adverse outcomes for mother or child. These cases add to the evidence that ferric carboxymaltose administration during pregnancy is effective and safe.